The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/nu12103060
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Hypertensive Effects of Peptides Derived from Rice Bran Protein

Abstract: Hypertension is one of the major risk factors for arteriosclerosis. Anti-hypertensive peptides derived from animal proteins, such as milk, eggs and fish, are well studied. Anti-hypertensive peptides have also been identified from plant proteins such as soybeans. Rice bran, a byproduct of white rice polishing, is rich in protein and its high protein efficiency ratio is well known. This review discusses the anti-hypertensive peptides identified from rice bran protein and their mechanisms. In addition, we describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Rice bran components have been reported to show anticancerous activity via various mechanisms involving antiapoptosis activity, anti‐inflammatory activity, chemo‐protective action, and so forth (Yu et al, 2019). Other phytoactive compounds of rice bran have also been documented to show other pharmaceutical activities like antidiabetic activity, anti‐inflammation, antihypertensive activity, cholesterol‐lowering activity, antioxidant activity, antimicrobial activity, and others, which elucidates the medicinal significance of rice bran in present time (Agista et al, 2021; Arab et al, 2011; Kahlon et al, 1993; Rao, Sugasini, et al, 2016; Shobako & Ohinata, 2020; Sivamaruthi et al, 2018). Munkong et al (2023) reported that in high‐fat diet‐fed mice, red rice bran extract mitigates the different pathological complications of dyslipidemia and hepatosteatosis by regulating the expression of various major genes involved in apoptosis, oxidative stress, inflammation, and lipid metabolism.…”
Section: Introductionmentioning
confidence: 92%
“…Rice bran components have been reported to show anticancerous activity via various mechanisms involving antiapoptosis activity, anti‐inflammatory activity, chemo‐protective action, and so forth (Yu et al, 2019). Other phytoactive compounds of rice bran have also been documented to show other pharmaceutical activities like antidiabetic activity, anti‐inflammation, antihypertensive activity, cholesterol‐lowering activity, antioxidant activity, antimicrobial activity, and others, which elucidates the medicinal significance of rice bran in present time (Agista et al, 2021; Arab et al, 2011; Kahlon et al, 1993; Rao, Sugasini, et al, 2016; Shobako & Ohinata, 2020; Sivamaruthi et al, 2018). Munkong et al (2023) reported that in high‐fat diet‐fed mice, red rice bran extract mitigates the different pathological complications of dyslipidemia and hepatosteatosis by regulating the expression of various major genes involved in apoptosis, oxidative stress, inflammation, and lipid metabolism.…”
Section: Introductionmentioning
confidence: 92%
“…The peptide (Leucine–Arginine–Alanine) obtained from Oryza sativa and chebulin (Aspartate–Glutamate–Asparagine-Serine–Lysine–Phenylalanine) from Terminalia chebula Retz has shown anti-hypertension activity by inhibiting ACE. The walnut and the fruit of Terminalia chebula Retz have been used as a food supplement in the control the hypertension (Shobako and Ohinata 2020 ; Sornwatana et al 2015 ).…”
Section: Non-infectious Diseasesmentioning
confidence: 99%
“…Thus, ACE inhibitors based on peptides derived from natural products are continuously and vigorously being investigated. In particular, casein from animal products and plant proteins from soybeans inhibit ACE activity in vitro [ 85 , 86 ]. Studies investigating functional foods with positive effects on hypertension are actively being conducted.…”
Section: Bioactivities and Human Health Benefits Of Cgjmentioning
confidence: 99%